Inhibiting Factors in the Prevention of Threatening Crimes in Paguyaman Pantai Sub-District - Niuwa, Riyan; Aprilia Kaluku, Julisa (Universitas Negeri Gorontalo, 2024)
The purpose of this research is to identify the factors that hinder the efforts to overcome the criminal act of threatening. The research method used by the author in this research is an empirical research method by taking a qualitative approach. The result of this research is that the prevention efforts carried out by the police initiative aim to handle and prevent the occurrence of criminal acts in an area, especially in Paguyaman Pantai Sub-district. However, countermeasures and prevention efforts are not only the responsibility of law enforcement officials, but can also be carried out by all members of the surrounding community. In Law Number 2 of 2002 concerning the Indonesian National Police, the roles and responsibilities of police officers are explained in accordance with the provisions in Article 13. In his case, the threats used included defamation through oral or written means, as well as threats to reveal secrets. The perpetrator also forces a person to give goods, in whole or in part, which belong to that person or another person. These threats also include attempts to get the person into debt or to cancel a debt.